2014
DOI: 10.1097/brs.0000000000000181
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Pain With Objective Quantification of Magnetic Resonance Images in Older Adults With Chronic Low Back Pain

Abstract: Study Design Cross sectional study. Objective The goal of this study is to identify relationships between objectively measured and subjectively scored parameters and reported pain. Summary of Background Data Studies have demonstrated the unreliability of MRI based parameters to identify pathological pain generators of chronic low back pain patients, but they were based on visual inspection and subjective assessment of lumbar disc features. Advancements in computer image analysis provide objective measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…A decrease in CSA of the paraspinal muscles has been widely reported to be related to chronic LBP in adults. [17][18][19][20] In contrast, no similar pathologic change could be seen in the paraspinous muscle adjacent to the minimally invasive retractor (Fig. 4).…”
Section: Discussionmentioning
confidence: 57%
“…A decrease in CSA of the paraspinal muscles has been widely reported to be related to chronic LBP in adults. [17][18][19][20] In contrast, no similar pathologic change could be seen in the paraspinous muscle adjacent to the minimally invasive retractor (Fig. 4).…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies have demonstrated associations between Modic changes and low back symptoms 20 , 21 and between Modic changes and lumbar spine kinematics. 19 , 22 24 To the best of our knowledge, no previous study has shown a relationship between Modic changes and axial neck pain in CK.…”
Section: Discussionmentioning
confidence: 96%
“…Since there is only one ODI score, but MRI measurements from five lumbar discs, an assumption was made that the most degenerated disc was the most likely source of pain. A similar approach was used earlier to study MRI biomarkers of LBP, but they used visual assessment to identify the most degenerated disc (Bechara et al, ). In this study, a quantitative degeneration score was derived using the equation below to obtain an objective measure of disc degeneration:1nDHI·nT2W…”
Section: Methodsmentioning
confidence: 99%